Prognostic impact of socioeconomic status compared to overall stage for HPV-negative head and neck squamous cell carcinoma. (August 2021) - Lenze, Nicholas R.; Farquhar, Douglas R.; Sheth, Siddharth; Zevallos, Jose P.; Lumley, Catherine; Blumberg, Jeffrey; Patel, Samip; Hackman, Trevor; Weissler, Mark C.; Yarbrough, Wendell G.; Olshan, Andrew F.; Zanation, Adam M.
Highlights: Low socioeconomic status (SES) predicts poor overall survival (OS) in HNSCC. Cancer stage has been considered the gold-standard prognosticator in HNSCC. Low SES may have similar prognostic ability to stage in HNSCC. Abstract: Objective: To estimate the relative prognostic ability of socioeconomic status (SES) compared to overall stage for HPV-negative head and neck squamous cell carcinoma (HNSCC) Materials and methods: Data were obtained from the Carolina Head and Neck Cancer Epidemiology Study (CHANCE). An empirical 4-category SES classification system was created. Cox proportional hazards models, survival gradients, Bayesian information criterion (BIC), and Harrell's C index were used to estimate the prognostic ability of SES compared to stage on overall survival (OS). Results: The sample consisted of 1229 patients with HPV-negative HNSCC. Patients with low SES had significantly increased risk of mortality at 5 years compared to patients with high SES (HR 3.11, 95% CI 2.07–4.67; p < 0.001), and the magnitude of effect was similar to overall stage (HR 3.01, 95% CI 2.35–3.86; p < 0.001 for stage IV versus I). Compared to overall stage, the SES classification system had a larger total survival gradient (35.8% vs. 29.1%), similar model fit (BIC statistic of 7412 and 7388, respectively), and similar model discriminatory ability (Harrell's C index of 0.61 and 0.64, respectively). The association between low SES and OS persisted after adjusting for age, sex, race, alcohol, smoking, overall stage, tumor site, and treatment in a multivariable model (HR 2.96, 95% CI 1.92–4.56; p < 0.001). Conclusion: SES may have a similar prognostic ability to overall stage for patients with HPV-negative HNSCC. Future research is warranted to validate these findings and identify evidence-based interventions for addressing barriers to care for patients with HNSCC.